Power and Persuasion: Analyzing Barack Obama’s ‘A More Perfect Union’ Speech - Wahyu Taufany; Rafi Muhammad Lubis; Muhammad Rizky Septiandri; Evaness Jocelym; T Tyrhaya Zein (Universitas Negeri Medan, 2025)
Barack Obama's A More Perfect Union speech is examined in this article using both a descriptive quantitative and rhetorical approach. The speech, delivered in 2008 during his presidential campaign, addressed racial tensions and called for togetherness in the midst of political upheaval. The study uses descriptive quantitative analysis to track linguistic patterns like word frequency and sentence structure, as well as rhetorical analysis to investigate Obama's use of ethos, pathos, and logos. According to the findings, Obama's strategic use of inclusive language, emotive appeals, and logical reasons strengthens his unifying message. This dual-method approach shows the speech's effectiveness in addressing polarizing issues while also providing insights into the broader effects of political discourse in promoting societal advancement. In